2007
DOI: 10.1016/j.neulet.2006.09.092
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to cell phone radiation up-regulates apoptosis genes in primary cultures of neurons and astrocytes

Abstract: The health effects of cell phone radiation exposure are a growing public concern. This study investigated whether expression of genes related to cell death pathways are dysregulated in primary cultured neurons and astrocytes by exposure to a working GSM (Global System for Mobile Communication) cell phone rated at a frequency of 1900 MHz. Primary cultures were exposed to cell phone emissions for 2 hrs. We used array analysis and real-time RT-PCR to show up-regulation of caspase-2, caspase-6 and Asc (apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 30 publications
3
83
0
2
Order By: Relevance
“…A significant change in cell proliferation in response to radiofrequency MFs, independent of thermal activity, has been reported in a cell culture experiment involving transformed human epithelial amnion cells (Velizarov et al 1999). Effects demonstrated in other studies include up-regulation of apoptosis genes, induction of reactive oxygen species, changes in protein conformation, the creation of stress proteins, and immune system disturbances (Zhao et al 2007;Sage and Carpenter 2009;NRPB 2003;Valentini et al 2007;Ruediger 2009). Caution is advised when interpreting these effects since numerous contradictory results are present in the literature.…”
Section: Mobile Phonesmentioning
confidence: 82%
“…A significant change in cell proliferation in response to radiofrequency MFs, independent of thermal activity, has been reported in a cell culture experiment involving transformed human epithelial amnion cells (Velizarov et al 1999). Effects demonstrated in other studies include up-regulation of apoptosis genes, induction of reactive oxygen species, changes in protein conformation, the creation of stress proteins, and immune system disturbances (Zhao et al 2007;Sage and Carpenter 2009;NRPB 2003;Valentini et al 2007;Ruediger 2009). Caution is advised when interpreting these effects since numerous contradictory results are present in the literature.…”
Section: Mobile Phonesmentioning
confidence: 82%
“…There are evidences of microwave exposure (1,71 GHz) influence on hsp70, c-jun, c-myc, and p21 levels in p53-deficient cells, but not in wild-type cells [79]. The EMF-induced changes of the transcript level of cell cycle regulatory and apoptosis-related genes were shown [80,81]. The 3.5 fold upregulation of mRNA stress-related transcription factor bZIP after exposure to 900 MHz microwaves was shown [82].…”
Section: The Action Of Emf On Intracellular Regulatory Systemsmentioning
confidence: 97%
“…It has been reported that sustained hyperglycemia induces early and severe β-cell dysfunction, and excess glucose causes β-cell loss via apoptosis [26]. Cell phone radiation can lead to the change of genetic regulation [27] and exacerbate oxidative stress [14,28]. Oxidative stress may more directly promote the onset of diabetes mellitus by decreasing insulin sensitivity and destroying the β-cell function within the pancreas [29].…”
Section: Ijomeh 2013;26(2) 239mentioning
confidence: 99%